PEMAKNAAN ISTILAH TINDAKAN BERSAMA (CONCERTED ACTION) DALAM PERJANJIAN PENETAPAN HARGA (STUDI PUTUSAN KPPU NOMOR 04/KPPU-I/2016 DAN NOMOR 15/KPPU-I/2019) - Monica Alina Yolanda; Anna Maria Tri Anggraini (Faculty of Law, Universitas Trisakti, 2023)
There is no explicit explanation of the term concerted action in Law Number 5 of 1999, but this term is often used by the KPPU to uncover cases of cartels and price fixing. Therefore, it is necessary to raise the issue of how to interpret the term concerted action in price fixing agreements according to Article 5 of Law Number 5 of 1999 and its implementing regulations; and how the KPPU applies the concerted action qualifications in Decision Number 04/KPPU-I/2016 and Number 15/KPPU-I/2019. The study uses a normative method, which is equipped with the result of interviews. The results of research show that the meaning of concerted action in the form of a meeting of minds from business actors is realized in verbal agreements which are followed up with actions aimed at gaining profit. The application of concerted action in KPPU decisions is to contain four (4) elements which include the meeting of mind, a verbal agreement followed by concerted action and changes in market conditions which cause price increases. The KPPU should complete the guidelines by explicitly stating joint actions, and business actors should prepare compliance guidelines as a means of preventing violations of Law Number 5 of 1999